Land Mafia Prevention and Eradication Efforts in Land Administration Law Perspective - Vani Wirawan; Yusriyadi Yusriyadi; Ana Silviana; Yeni Widowaty (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The existence of a land mafia can almost investment and economic growth because the crimes they commit include land cases with a broad dimension, so prevention and eradication are needed in the administrative land area. This study aims to develop efforts to prevent and eradicate future land mafia in the land administration area. This research is descriptive-analytical with a sociolegal approach. This Study obtained alternative efforts to prevent and eradicate future land mafia, namely the idea of changing land registration from a negative publication system to a positive publication system.